Kiat Praktis Penguasaan Bahasa Indonesia Resmi untuk Guru dan Siswa demi Komunikasi Sekolah yang Efektif (Jurnal PGSD Universitas Lamappapoleonro, 2025)
This study aims to improve formal Indonesian language communication skills in schools through a participatory approach. The main problems identified include teachers' limited understanding of formal Indonesian language rules, students' limited skills in using formal language varieties, minimal awareness of the importance of using standard Indonesian, and lack of practical strategies to improve school communication quality. The research method employed a descriptive qualitative approach with participatory techniques, involving 27 participants consisting of 15 teachers (55.6%) and 12 students (44.4%). Data were collected through observation, semi-structured interviews, pre-test and post-test questionnaires, and documentation. The training program was implemented in three stages: socialization and needs diagnosis, intensive training and guided practice, and mentoring and evaluation. Results showed significant improvement in all competency aspects with an average increase of 45.1%, including conceptual understanding (36.5%), standard vocabulary usage (60.8%), effective sentence construction (52.1%), and spelling and punctuation application (30.1%). Written document quality improved from 32% to 91%, while 96.3% of participants rated the program as highly beneficial. This program successfully transformed school communication culture from informal to formal-professional and can serve as a replication model for other schools in efforts to improve Indonesian language communication quality in educational settings
Keywords: Formal Indonesian Language; Communication; School